Aging, hormones and receptors - Hill, M; Třískala, Z; Honců, P; Krejčí, M; Kajzar, J; Bičíková, M; Ondřejíková, L; Jandová, D; Sterzl, I (Physiological research, 2020)
Ageing is accompanied by deterioration in physical condition and a number of physiological processes and thus a higher risk of a range of diseases and disorders. In particular, we focused on the changes associated with aging, especially the role of small molecules, their role in physiological and pathophysiological processes and potential treatment options. Our previously published results and data from other authors lead to the conclusion that these unwanted changes are mainly linked to the hypothalamic-pituitary-adrenal axis can be slowed down, stopped, or in some cases even reversed by an appropriate treatment, but especially by a life-management adjustment.
Keywords: stárnutí; Receptors, Cell Surface; Hormones; hormony; Aging; Humans; Animals; Hypothalamo-Hypophyseal System; lidé; systém hypotalamus-hypofýza; Small Molecule Libraries; receptory buněčného povrchu; zvířata; systém hypofýza - nadledviny; knihovny malých molekul; Pituitary-Adrenal System